2016
DOI: 10.1128/iai.01396-15
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Emp Pilus Subunits of Enterococcus faecium in Biofilm Formation, Adherence to Host Extracellular Matrix Components, and Experimental Infection

Abstract: cEnterococcus faecium is an important cause of hospital-associated infections, including urinary tract infections (UTIs), bacteremia, and infective endocarditis. Pili have been shown to play a role in the pathogenesis of Gram-positive bacteria, including E. faecium. We previously demonstrated that a nonpiliated ⌬empABC::cat derivative of E. faecium TX82 was attenuated in biofilm formation and in a UTI model. Here, we studied the contributions of the individual pilus subunits EmpA, EmpB, and EmpC to pilus archi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Literature concerning biofilm‐formation of the other pathogens only detected by sonification is scarce. These rather rare pathogens definitely need to be further investigated in regards of biofilm formation …”
Section: Discussionmentioning
confidence: 99%
“…Literature concerning biofilm‐formation of the other pathogens only detected by sonification is scarce. These rather rare pathogens definitely need to be further investigated in regards of biofilm formation …”
Section: Discussionmentioning
confidence: 99%
“…Cultures grown to an OD 600 of 1.0 Ϯ 0.1, as described above for the PBP5 Western blot assay, were used for RNA extraction, performed as previously described (30). Primers F-pbp5-218 and R-pbp5-218 (Table S2) were used for generating a pbp5 hybridization probe, which amplifies a fragment that is identical in 217 of the 218 nucleotides between pbp5-S and pbp5-R. Northern blot analyses were carried out as reported before (31,32).…”
Section: Methodsmentioning
confidence: 99%
“…In lactobacilli, many of the characterized attachment factors are surface moonlighting proteins, that recognize a spectrum of host receptors, among the most common being extracellular matrix components (ECM) . Being ubiquitously and profusely distributed, the ECM proteins are also attractive targets for adhesion and invasion by various human pathogen microorganisms . It has been reported that many of them use moonlighting proteins as adhesin .…”
Section: Introductionmentioning
confidence: 99%